Effective Pedagogy in Primary Education: A Review of Current Literatures - Ciptro Handrianto; Ahmad Jazimin Jusoh; Yanti Karmila Nengsih; Alfurqan Alfurqan; Muslim Muslim; Amayra Tannoubi (Abjadia, 2021)
The implementation of effective pedagogy in instructional strategies is an interesting discussion among educationists due to the rapidly transformation in educational context. The aims of this study is to identify the current literature related to effective pedagogy in primary education and highlights its categories in teaching learning situation.  The method used in this study is literature approach by reviewing 15 current journal articles in five years, from 2017 to May 2021.  The study shows that several characteristics of effective pedagogy still attract the researchers to discuss in their papers during the current five years. The fundamental characteristics of effective pedagogy frequently highlighted in primary education are: classroom management, teachers` competences, instructional strategies, valuable learning, and students` achievement. The conclusion of this study, several current literatures highlight that the effective pedagogy is the general view of teachers to specify their action to carry out the new strategies, approaches, and methods to fostering primary school pupils.